2020
DOI: 10.1111/cns.13534
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl pyruvate improves white matter remodeling in rats after traumatic brain injury

Abstract: Background Severe traumatic brain injury (TBI) results in long‐term neurological deficits associated with white matter injury (WMI). Ethyl pyruvate (EP) is a simple derivative of the endogenous energy substrate pyruvate with neuroprotective properties, but its role in recovery from WMI has not been explored. Aims This study examines the effect of EP treatment on rats following TBI using behavioral tests and white matter histological analysis up to 28 days post‐injury. Materials and Methods Anaesthetised adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…The rotarod test was performed to evaluate the balance and sensorimotor coordination ( Mao et al, 2020 ). After the animals were placed on the rods, the rods began to accelerate to 40 r/min within 30 s, and this speed was maintained until 300 s. The duration on the rods was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The rotarod test was performed to evaluate the balance and sensorimotor coordination ( Mao et al, 2020 ). After the animals were placed on the rods, the rods began to accelerate to 40 r/min within 30 s, and this speed was maintained until 300 s. The duration on the rods was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Besides gray matter, white matter is also the main target of TBI closely linked to neurological impairment [ 21 ]. Firstly, MBP and NF-200 were stained to observe myelin and neurofilament changes in the striatum after TBI (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to short-term behaviors, we observed long-term behaviors and neuronal tissue loss, providing long-term neuroprotection evidences for cordycepin. TBI-induced WMI is positively correlated with neurological deficits, reducing WMI helps improve neurological functions [ 21 ]. We observed that cordycepin reserved the morphology of white matter and neurofilament on 35 days after TBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroinflammatory responses (e.g., microglia/macrophage activation) could be induce by TBI, which is regarded as a key factor in the secondary injury cascade following TBI. Immunofluorescence staining is a classic method to investigate the mechanism of TBI-induced neuroinflammatory responses (Readnower et al, 2010;Villapol et al, 2017;Takahata et al, 2019;Mao et al, 2021). By double-labeling immunofluorescence, the levels of the lipid peroxidation marker 4-hydroxynonenal (4-HNE) and the protein nitration marker 3-nitrotyrosine (3-NT) in brain sections after exposure to blast have been determined (Readnower et al, 2010).…”
Section: Imaging Of Brain Cells and Tissuesmentioning
confidence: 99%